2006
DOI: 10.1111/j.1365-2842.2006.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occlusal contact localization on the stress distribution in complete maxillary denture

Abstract: The fracture of acrylic resin dentures is an unresolved problem in removable prosthodontics despite many efforts to determine its cause. Unfavourable occlusion could be playing an important role in the fracture of the denture. The aim of this study was to investigate the effect of occlusal contact localization on the stress distribution in complete maxillary denture bases utilizing two-dimensional finite element analysis. The results of this study have shown that maximum compressive stresses in a complete maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
1
27
1
1
Order By: Relevance
“…The results of the present study agree with those of Ates et al [13] who stated that shifting the occlusal contacts to a more buccal localization resulted in an increase of the calculated stresses towards midline (tensile) of the palate in complete maxillary denture. They concluded that the buccal placement of occlusal contacts may play a role in fatigue fracture of the complete maxillary denture.…”
Section: Discussionsupporting
confidence: 95%
“…The results of the present study agree with those of Ates et al [13] who stated that shifting the occlusal contacts to a more buccal localization resulted in an increase of the calculated stresses towards midline (tensile) of the palate in complete maxillary denture. They concluded that the buccal placement of occlusal contacts may play a role in fatigue fracture of the complete maxillary denture.…”
Section: Discussionsupporting
confidence: 95%
“…It is well known that an edentulous patient can only exert occlusal forces at a level of 15 -25% of dentate patients and an acrylic complete denture bears tensile stress values about 48-62 MPa, and compressive stress values about 75 MPa considering local stress concentrations (Ates et al 2006). As a consequence, the denture is not expected to fracture under functional masticatory forces (Beyli and von Fraunhofer 1981;Ates et al 2006). However, fractures in dentures are reported.…”
Section: Introductionmentioning
confidence: 97%
“…Many methods of experimental stress analysis, such as brittle coating, photoelastic models, strain gauges, have been used to examine the stress distribution in complete maxillary dentures as in Vlissidis (2006, 2009), as well as numerical models applying finite element methods (FEM; Beyli and von Fraunhofer 1981;Darbar et al 1996;Hengyi et al 2004;Ates et al 2006;Prombonas and Vlissidis 2009;Cheng, Li, et al 2010). All these studies show that the stress concentrates in the anterior palatal areas of maxillary dentures.…”
Section: Introductionmentioning
confidence: 98%
“…FEA techniques have recently been introduced into the analysis of the deformation of complete dentures [14,18,19]. An FEA solution is only approximate due to the use of discrete mesh models, which are seldom exact representations of the physical problem, although the errors can be reduced by using a sufficiently fine mesh [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The stresses and strains in the palatal region of the CUDs have been measured experimentally using several methodologies, including brittle coatings [1], strain gauges [2][3][4][5][6][7][8][9], photoelastic models [10,11], holography [12], a scanning electron microscope replica technique [13], and simulations such as finite element analysis (FEA) [14]. The above researches referred to the maximum values of strains and stresses under a single load (maximum load), without taking into account the realities of mastication which takes place under fluctuated loading.…”
Section: Introductionmentioning
confidence: 99%